Facile simultaneous synthesis of tetraaniline nanostructures/silver nanoparticles as heterogeneous catalyst for the efficient catalytic reduction of 4-nitrophenol to 4-aminophenol. Issue 37 (9th June 2020) - Botsa, Sathish Mohan; Kumar, Yarramsetti Pavan; Basavaiah, Keloth
Abstract : Nanocomposites of tetraaniline/silver nanoparticles were synthesised using an interfacial polymerisation method. The catalytic activity was investigated for the model reduction of 4-nitrophenol to 4-aminophenol in the presence of excess sodium borohydride. Abstract : Nanocomposites of tetraaniline (TAN) nanostructures/silver nanoparticles (Ag NPs) were synthesized by an interfacial polymerization method using N -phenyl-1, 4-phenylenediamine (NPPD), AgNO3 and ammonium persulphate (APS) as monomer, oxidizing agent in immiscible solvent toluene–water respectively. The structure and morphology of the as-prepared TAN and Ag NPs were investigated by UV-visible spectroscopy, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), and thermogravimetry (TG). The results of FTIR spectroscopy confirmed the formation of TAN and Ag NPs and those of XRD showed the presence of the face centred cubic (fcc) phase of Ag NPs. The FESEM and TEM images gave direct evidence that Ag NPs stabilized with the TAN nanostructures. TGA indicated the enhanced thermal stability of the nanocomposites (NCs). The catalytic activity of TAN/Ag NCs was investigated for the model reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) in the presence of excess sodium borohydride.